Berbagai Faktor Yang Berhubungan Dengan Kejadian Gangguan Fungsi Paru Dalam Ruang Kerja (Studi Kasus Pekerja Industri Rumahan Electroplating di Kecamatan Talang Kabupaten Tegal) - Wulandari, Diah Rahayu; Hadisaputro, Soeharyo; Suhartono, Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: electroplating home industry  use chromium as the base material. Chromium is used in the form of hexavalent chromium, which has toxic effects on health.  Electroplating workers exposed chromium through the air into the lungs through inhalation. Objective: Describe the various factors assosiated  to the pulmonary dysfunction  in a workplace at  workers of electroplating home industry . Methods: This study was an observational study with cross sectional approach  on 31 electroplating workers with total sampling of each industry. Vital Lung Capacity Measurements with a spirometer with SpyroAnalyzer type ST-75. Dust levels of Chromium with High Volume Sampler. Results: Results minimal amount of dust in the air of 0.0731 μg/m3, the maximum value of dust concentration in the air is 1.8433 μg/m3 μg/m3 with a mean of 0.774357. Multivariate analysis showed a variable duration of exposure to chromium is the most influential variable on the incidence of pulmonary dysfunction, (p = 0.010) with 95% CI (2.11 to 228.56), odds ratio (Exp B) = 21.97. Conclusion: The factor shown to be associated with pulmonary dysfunction in workers chromium electroplating is a duration of exposure to chromium more than 4 hours a day. Keywords: Electroplating, pulmonary dysfunction, chromium.